Pembelajaran Sejarah Berbasis Proyek dalam Meningkatkan Kreativitas dan Kolaborasi Siswa Kelas X Kerajaan Hindu-Buddha di SMA Negeri 16 Semarang - Nur'afifi, Wahyu laila; Ba'in, Ba'in (Dinasti Research, 2026)
This study examines the application of the Project Based Learning (PjBL) model in learning the history of the Hindu-Buddhist Kingdom to enhance student creativity and collaboration. The study was conducted using a qualitative approach at SMA Negeri 16 Semarang in class X6, which consisted of 36 students and divided into seven heterogeneous groups. Data collection techniques used included non-participant observation, in-depth semi-structured interviews with the history teacher and seven student representatives, and documentation studies. Data analysis used the interactive model of Miles and Huberman which includes collection, reduction, presentation, and drawing conclusions, while data validity was guaranteed through triangulation of sources and methods. The results showed that the implementation of PjBL took place systematically through six stages and actively involved students from planning to presentation. PjBL contributed to the development of student creativity in four dimensions, namely fluency, flexibility, originality, and elaboration, which were reflected in the unique variations of Canva-based visual presentations from each group. Students' creativity was also evident in the visual documentation of the project in the form of photos of group members portraying royal figures according to their respective themes, including the use of costumes made by group members as a form of realization of historical material so that students could more easily imagine and understand the conditions of Hindu-Buddhist kingdoms when presenting the material. Collaboration skills developed through teamwork productivity, active contribution, balanced communication, and joint decision-making through deliberation. Students' responses to this learning were very positive because it was considered more interesting and meaningful than conventional approaches, and provided benefits in the form of a deeper understanding of the material, improved public speaking skills, strengthened cooperation, and expanded social relations